2020
DOI: 10.1037/dev0001010
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual language broker profiles and academic competence in Mexican-origin adolescents.

Abstract: We advance a tripartite framework of language use to encompass language skills, the practice of language skills, and the subjective experiences associated with language use among Mexican-origin adolescents who function as language brokers by translating and interpreting for their English-limited parents. Using data collected over 2 waves from a sample of 604 adolescents (Wave 1: M age ϭ 12.41, SD ϭ 0.97), this study identified 4 types of bilingual language broker profiles that capture the tripartite framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 46 publications
(97 reference statements)
3
25
0
Order By: Relevance
“…Kim et al (2018) used LPA to identify adolescent profiles by integrating broker experiences and contextual stressors, and identified protective and risk profiles. Using a three-part language use framework (proficiency, brokering frequency, subjective brokering experiences), Kim et al (2020) identified four profiles (efficacious, moderate, ambivalent, nonchalant) in Mexican-American adolescent bilingual brokers. This research indicates that bilingual brokering experiences are manifold.…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…Kim et al (2018) used LPA to identify adolescent profiles by integrating broker experiences and contextual stressors, and identified protective and risk profiles. Using a three-part language use framework (proficiency, brokering frequency, subjective brokering experiences), Kim et al (2020) identified four profiles (efficacious, moderate, ambivalent, nonchalant) in Mexican-American adolescent bilingual brokers. This research indicates that bilingual brokering experiences are manifold.…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…The current study utilized data collected from 2012 to 2015. Participants were 604 Mexican‐origin adolescents with at least one immigrant parent recruited from a metropolitan city in central Texas (Kim et al., 2020). Data collection occurred during Barack Obama’s presidency, and the political climate of Texas and the larger US was mixed, particularly regarding immigration.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we included adolescents’ self-reported age, gender, nativity (i.e., foreign-born or U.S.-born), and Spanish and English proficiency as covariates in our study. Specifically, adolescents’ proficiency in reading, writing, speaking, and understanding Spanish and English was assessed using a five-point scale validated for use with Mexican-origin adolescents (Kim et al, 2020 ), ranging from 1 = not well to 5 = extremely well (Cronbach’s alphas = 0.81 for Spanish and 0.82 for English). Past studies have found that self-report measures of language proficiency are correlated with objective measures of language proficiency (Dunn & Fox Tree, 2009 ).…”
Section: Methodsmentioning
confidence: 99%